PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, INTENSITAS MODAL, UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITIES TERHADAP KONSERVATISME AKUNTANSI - Kadek Ayu Permaidya Sari (UNHI Press, 2021)
The company is accountable for its operational activities by issuing financial reports. One form of management accountability in meeting the interests of internal and external parties as a consideration for decision making can be seen in the preparation of the company's financial statements. Problems that usually occur in a company usually involve managers and investors, where there will be actions in displaying small company profits in order to create a conservative impression in accounting. Conservatism in accounting implies the existence of asymmetric verification requirements between the recognition of profit and loss. The purpose of this research is to examine the effect of managerial ownership structure, capital intensity, firm size and growth opportunities on accounting conservatism. The population in this study were manufacturing companies listed on the BEI in 2017-2019 which included 25 companies as samples within 3 years, so that 75 data were processed. In this study, researchers used a purposive sampling method. With the data analysis technique, namely using multiple linear regression analysis techniques with the help of the SPSS 21.00 program for windows statistics. The results of data processing, managerial ownership structure has no significant effect on accounting conservatism. Capital intensity does not have a significant effect on accounting conservatism. Firm size has a positive and significant effect on accounting conservatism. Grownth opportunities have a negative and significant effect on accounting conservatism.